Phlebotominae (Diptera : Psycodidae) fauna in the Chaco region and Cutaneous Leishmaniasis transmission patterns in Argentina - Salomón, Oscar Daniel (2008)
Fil: Salomón, Oscar Daniel. ANLIS Dr.C.G.Malbrán. Centro Nacional de Diagnóstico e Investigación en Endemo-Epidemias; Argentina.